Association of Left Ventricular Systolic Function and Vasopressor Support With Survival Following Pediatric Out-of-Hospital Cardiac Arrest*. Issue 2 (February 2015) - Conlon, Thomas W.; Falkensammer, Christine B.; Hammond, Rachel S.; Nadkarni, Vinay M.; Berg, Robert A.; Topjian, Alexis A.
<x xml:space="preserve">Abstract</x> Objectives: To characterize the association of hospital discharge survival with left ventricular systolic function evaluated by transthoracic echocardiography and vasoactive infusion support following return of spontaneous circulation after pediatric out-of-hospital cardiac arrest. Design: Retrospective case series. Setting: Single-center tertiary care pediatric cardiac arrest and critical care referral center. Patients: Consecutive out-of-hospital cardiac arrest patients less than 18 years surviving to PICU admission who had a transthoracic echocardiography obtained by the clinical team within 24 hours of admission from January 2006 to May 2012. Interventions: None. Measurements and Main Results: Fifty-eight patients had a post–return of spontaneous circulation transthoracic echocardiography performed within 24 hours of admission. The median time from return of spontaneous circulation to echo was 6.5 hours (interquartile range, 4.7, 15.0 hr). Left ventricular systolic function was decreased in 24 of 58 patients (41%). The mortality rate was 67% (39 of 58). Thirty-six patients (62%) received vasoactive infusions at the time of transthoracic echocardiography, and increased vasopressor inotropic score was associated with increased mortality on univariate analysis (p < 0.001). After controlling for defibrillation, vasopressor inotropic score, and interaction between vasopressor inotropic score and left ventricular systolic function, decreased left ventricular systolic function was associated with increased mortality (odds ratio, 13.7; 95% CI, 1.54–122). Conclusions: In patients receiving transthoracic echocardiography within the first 24 hours following return of spontaneous circulation after pediatric out-of-hospital cardiac arrest, decreased left ventricular systolic function and vasopressor use were common. Decreased left ventricular systolic function was associated with increased mortality.